Project Based Learning for Creativity Development Using Recycled Materials: Pembelajaran Berbasis Proyek untuk Pengembangan Kreativitas Menggunakan Bahan Daur Ulang - Firdaus, Dwi Nur Saputri Maulana; Setiyawan, Enik (Indonesian Journal of Education Methods Development, 2025)
Background: The need to promote student creativity in science learning remains a challenge, particularly in classrooms where teacher-centered instruction still dominates. Specific Background: At SDN Kemiri Sidoarjo, unused plastic bottles accumulate in classrooms, indicating missed opportunities for contextual learning activities. Gap: Previous studies have explored Project Based Learning (PjBL), but limited research integrates PjBL with recycled materials to stimulate creativity in elementary science learning. Aims: This study aims to describe how PjBL using recycled plastic bottles contributes to the creativity of fourth-grade students. Results: Using a pre-experimental One-Shot Case Study design, data from 30 students were collected through structured observation. The findings show an increase in the average creativity score to 59.2%, categorized as “Good Creativity,” indicating a moderate level of improvement across fluency, flexibility, originality, and elaboration. Novelty: This research combines PjBL with direct utilization of plastic waste, creating hands-on, environmentally oriented learning that strengthens creativity indicators. Implications: The study provides practical insights for teachers to integrate recycled materials into project-based science activities to foster creativity more effectively. Highlights:• Recycled materials support contextual creativity• PjBL fosters independent project construction• Creativity improves at a moderate level Keywords: Project Based Learning, Creativity, Recycled Materials, Elementary Science, Observation